2022
DOI: 10.1124/jpet.122.001335
|View full text |Cite
|
Sign up to set email alerts
|

Istaroxime Metabolite PST3093 Selectively Stimulates SERCA2a and Reverses Disease-Induced Changes in Cardiac Function

Abstract: Heart failure (HF) therapeutic toolkit would strongly benefit from the availability of ino-lusitropic agents with a favorable pharmacodynamics and safety profile. Istaroxime is a promising agent, which combines Na + /K + pump inhibition with SERCA2a stimulation; however, it has a very short half-life and extensive metabolism to a molecule, named PST3093. The present work aims to investigate whether PST3093, still retains the pharmacodynamic and pharmacokinetic properties of its parent compound. We studied PST3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…Next, we evaluated SERCA2a function in the context of an intact myocyte. To improve mechanistic interpretation of the mutation effect, studies with an agent known to increase SERCA2a function by preventing its interaction with PLN 10 were included. SERCA2a function may have different impact on intracellular Ca 2+ dynamics at different heart rates; therefore, the rate‐dependency of changes in Ca 2+ dynamics was also evaluated in a separate set of CMs field‐stimulated at four rates between 1 and 2 Hz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we evaluated SERCA2a function in the context of an intact myocyte. To improve mechanistic interpretation of the mutation effect, studies with an agent known to increase SERCA2a function by preventing its interaction with PLN 10 were included. SERCA2a function may have different impact on intracellular Ca 2+ dynamics at different heart rates; therefore, the rate‐dependency of changes in Ca 2+ dynamics was also evaluated in a separate set of CMs field‐stimulated at four rates between 1 and 2 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…The view that hyperdynamic Ca 2+ handling reflects enhanced SERCA2a activity is reinforced by (1) increased Ca 2+ sensitivity (lower Kd Ca ) of SERCA2a ATPase activity in myocardial homogenates; (2) similarity with the effect of PST‐3093, a SERCA2a stimulator. The latter is known to increase SERCA2a activity by weakening its interaction with PLN, 10 thus suggesting reduced affinity for SERCA2a as a mechanism of PLN R14del behavior. In the PLN R14del heterozygous state, PST‐3093 should have retained part of its stimulatory effect by displacing residual WT PLN.…”
Section: Discussionmentioning
confidence: 99%
“…Of all these SERCA2a activators only istaroxime, a known Na + /K + transporting ATPase inhibitor as well as an inotropic/lusitropic agent acting to enhance SERCA2a activity, has been in phase IIb clinical trials for treatment of heart failure 45,46 . However, because of its unsuitability for human usage (poor gastrointestinal absorption, high clearance rate, and extensive metabolic transformation) 46 , istaroxime derivatives were designed from QSAR studies and a new promising class of SERCA2a activators has been identified 47,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…The view that hyperdynamic Ca 2+ handling reflects enhanced SERCA2a activity is reinforced by 1) increased Ca 2+ sensitivity (lower Kd Ca ) of SERCA2a ATPase activity in myocardial homogenates; 2) similarity with the effect of PST-3093, a SERCA2a stimulator. The latter is known to increase SERCA2a activity by weakening its interaction with PLN, 9 thus suggesting reduced affinity for SERCA2a as a mechanism of PLN R14del effects. In the PLN R14del heterozygous state, PST-3093 should have retained part of its stimulatory effect by displacing residual WT PLN.…”
Section: Intracellular Ca 2+ Dynamicsmentioning
confidence: 99%
“…The "superinhibition" theory motivated us to test reversal of PLN R14del +/phenotype by a recently developed compound (PST-3093) that selectively stimulates SERCA2a by antagonizing its interaction with PLN. 9 Strikingly, human iPS-derived cardiomyocytes (hiPS-CMs) from a heterozygous human mutation carrier displayed a hyperdynamic Ca 2+ handling instead, a phenotype that obviously is incompatible with the SERCA2a "superinhibition". Notably, PST-3093 mimicked the effect of the mutation when applied to the WT hiPS-CMs, but it was ineffective in mutant ones.…”
Section: Introductionmentioning
confidence: 99%